Variation in COVID‐19 Mortality Across 117 US Hospitals in High‐ and Low‐Burden Settings. Issue 4 (17th March 2021) - Block, Brian L; Martin, Thomas M; Boscardin, W John; Covinsky, Kenneth E; Mourad, Michele; Hu, Lissy L; Smith, Alexander K
Abstract : Some hospitals have faced a surge of patients with COVID‐19, while others have not. We assessed whether COVID‐19 burden (number of patients with COVID‐19 admitted during April 2020 divided by hospital certified bed count) was associated with mortality in a large sample of US hospitals. Our study population included 14, 226 patients with COVID‐19 (median age 66 years, 45.2% women) at 117 hospitals, of whom 20.9% had died at 5 weeks of follow‐up. At the hospital level, the observed mortality ranged from 0% to 44.4%. After adjustment for age, sex, and comorbidities, the adjusted odds ratio for in‐hospital death in the highest quintile of burden was 1.46 (95% CI, 1.07‐2.00) compared to all other quintiles. Still, there was large variability in outcomes, even among hospitals with a similar level of COVID‐19 burden and after adjusting for age, sex, and comorbidities. Abstract :